Alginate–gum Arabic beads for encapsulation of longan extract: Improving efficiency, stability, and safety - Fuangchoom, Varunya; Narkprasom, Nukrob; Rattanawongwiboon, Thitirat; Narkprasom, Kanjana (Journal of Food Technology Research, 2026)
Phenolic compounds from longan (Dimocarpus longan Lour.) extract possess strong antioxidant properties but are highly unstable during processing and storage, limiting their application in functional foods. This study aimed to develop an alginate–gum Arabic encapsulation system to enhance the efficiency, stability, and microbial safety of longan phenolic compounds. Beads were produced using an extrusion technique with 1.5% (w/v) sodium alginate and 4% (w/v) calcium chloride as the optimal gelling condition, and gum Arabic was incorporated as a co-polymer to improve bead performance. The formulation containing gum Arabic exhibited the highest encapsulation efficiency (74.9%), and stability evaluations revealed superior retention of phenolic compounds under acidic conditions (pH 2), with a more controlled release profile compared to neutral and alkaline environments. To address microbial safety, gamma irradiation at 5 and 7.5 kGy was applied; a dose of 5 kGy increased bead firmness, whereas 7.5 kGy achieved complete sterilization without compromising structural integrity or functional properties. These findings indicate that the integration of alginate with gum Arabic significantly enhances both encapsulation performance and bioactive stability, while gamma irradiation serves as an effective non-thermal sterilization method. The developed system demonstrates strong potential for application as a delivery platform in functional food and nutraceutical formulations requiring stability and safety assurance.